Analisis Perbandingan Kinerja Pegawai PNS Dan Non PNS Dinas XXX Kota XXX - Vadya Levita Putri; Askolani Askolani; Kusuma Agdhi Rahwana (Pusat Riset dan Inovasi Nasional, 2023)
Civil Servants (PNS) are elements of the state apparatus whose duty is to provide services to the public in a professional, honest, fair and equitable manner in the implementation of state, government and development tasks. Meanwhile, Honorary Personnel has lively developed into a new paradigm in the agency environment in addition to other honorary personnel after Civil Servants even though basically the work done is almost the same as Civil Servants in general, the only difference is that Non-Civil Servants (honorary) employees rarely occupy important structural positions in the agency. Because they only help those who are assigned directly by the superiors and heads of sections of an agency. So that both civil servants and non-civil servants in the XXX City Education Office must have quality performance that is able to carry out their duties as government officials in accordance with the duties assigned. The purpose of this study was to determine how the performance of civil servants and non-civil servants at the XXX City Education Office, whether there are differences in performance between civil servants and non-civil servants at the XXX City Education Office, and what factors affect the performance of civil servants and non-civil servants at the XXX City Education Office. The research method used is quantitative method and the data collection method in this study is by distributing questionnaires. the sample in this study were civil servants and non-civil servants at the XXX City Education Office, namely 42 civil servants and 42 non-civil servants. The data analysis technique in this study uses Satistical Product and Service Solution (SPSS) with T-Test analysis.